2022
DOI: 10.1002/bmc.5458
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of four major flavonoids in normal and chronic gastritis rats after oral administration of different combinations of Banxia Xiexin decoction

Abstract: Chronic gastritis (CG) has become a major threat to human health. Banxia Xiexin Decoction (BXXXD) has been used clinically to treat gastritis by acting on the spleen and stomach for thousands of years. Baicalin, wogonoside, liquiritin and liquiritigenin are the main bioactive flavonoids of BXXXD. A rapid, sensitive and selective HPLCtriple quadrupole (TQ)-MS/MS method was developed to simultaneously quantify the four flavonoids in rat plasma in this study. With salidroside as internal standard (IS), plasma sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Some metabolites of HCl conjugate might be transformed from LQ under the action of gastric acid after intragastric administration. LQ reached C max within 1 h, which was in good agreement with those from previous work (Wan et al, 2020; Wang et al, 2021; Zhou et al, 2022). Compared with the peak area–time curves, the metabolites of LQ reached C max within 5 h and were eliminated slowly, which explained the poor absorption and rapid elimination of LQ.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some metabolites of HCl conjugate might be transformed from LQ under the action of gastric acid after intragastric administration. LQ reached C max within 1 h, which was in good agreement with those from previous work (Wan et al, 2020; Wang et al, 2021; Zhou et al, 2022). Compared with the peak area–time curves, the metabolites of LQ reached C max within 5 h and were eliminated slowly, which explained the poor absorption and rapid elimination of LQ.…”
Section: Discussionsupporting
confidence: 93%
“…Some metabolites of HCl conjugate might be transformed from LQ under the action of gastric acid after intragastric administration. LQ reached C max within 1 h, which was in good agreement with those from previous work(Wan et al, 2020;Wang et al, 2021;Zhou et al, 2022). Compared with the F I G U R E 4 Proposed metabolic pathways for liquiritin (LQ) in acute myocardial infarction (AMI) rats.…”
supporting
confidence: 88%
“…Recent research by Zhou et al revealed systematic PK data of BXD under the pathological settings of chronic gastritis. [ 126 ] In comparison to the control group, the PK parameters of baicalin, wogonoside, liquiritin, and liquiritigenin in rats with chronic gastritis altered dramatically, with significant reductions in C max , AUC (0-t) , and AUC (0-∞) . The T 1/2 of wogonoside and liquiritin were also considerably decreased in rats with chronic gastritis.…”
Section: Pk Investigationmentioning
confidence: 99%